Making the most of markets: The role of IFIs - Nicholas H. Stern; Hans Peter Lankes (EIB Papers, 1998)
Since the World Bank and the International Monetary Fund were launched at Bretton Woods more than 50 years ago, and the regional development banks in subsequent decades, the world economy has changed in important respects. In considering the role of international financial institutions (IFIs), two changes are of particular significance. First, 'globalisation' implies that foreign trade and private capital now play a far greater role in economic development than before. Partly as a result, world real interest rates have increased markedly. Second, the poor performance of statist models of development has led to a re-examination of the role of the state and motivated a strong shift towards private, market-based approaches. As a result of these changes, the private sector and private, international finance have become prime agents of economic development. In this article, we discuss how IFIs can pursue their mandates by creating the conditions for the right kind of market-oriented growth and by forming partnerships with the private sector. We argue that partnership with the private sector calls for significant adjustments in the modus operandi of IFIs, as well as for clear principles of engagement. IFIs must complement and catalyse private finance, they must not displace it. A clearly defined approach to supporting private sector development will carry IFIs well into the 21st century.
Keywords: 330; Entwicklungsbank; Entwicklungsorganisation; Internationaler Finanzmarkt; Welt